2012
DOI: 10.1111/j.1540-5885.2012.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Performativity of the “Ambidextrous Organizations” Theory: Neither Lost in nor Lost before Translation

Abstract: Ambidextrous organizations succeed both in incremental and discontinuous innovation. However, there is little direct empirical evidence on how managers implement the principles of the “ambidextrous organizations” theory to dynamically align the structure and culture of ambidextrous organizations. Our study does not focus on analyzing the factors that give rise to organizational ambidexterity but focuses on analyzing whether the factors suggested by prior theorizing on “ambidextrous organizations” are implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 130 publications
2
53
0
Order By: Relevance
“…Similar to March, 17 we define radical innovation as the capacity to pursue variation in existing knowledge, and incremental innovation as the capacity to refine and improve existing knowledge. As such, it addresses noted gaps in the literature that call for a more process-based perspective of the ambidextrous organization, 18 as our results emphasize the potential for social media crowdsourcing to enable dual exploration and exploitation processes during ideation stages of innovation.…”
supporting
confidence: 56%
“…Similar to March, 17 we define radical innovation as the capacity to pursue variation in existing knowledge, and incremental innovation as the capacity to refine and improve existing knowledge. As such, it addresses noted gaps in the literature that call for a more process-based perspective of the ambidextrous organization, 18 as our results emphasize the potential for social media crowdsourcing to enable dual exploration and exploitation processes during ideation stages of innovation.…”
supporting
confidence: 56%
“…Thus, firms that may be great at exploring may not necessarily be good at exploiting (Chesbrough, Vanhaverbeke, and West, 2006). Other firms may have the opposite but equally daunting dilemma; their focus on exploiting innovations for existing customers prevents them from exploring more radical, innovative solutions for development (Durisin and Todorova, 2012). There is evidence that this was the case in the hard disk drive industry (Christensen and Rosenbloom, 1995).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…As a consequence, many firms tend to develop capabilities that enable them to develop exploitative innovations or exploratory innovations, but not both. However, doing so may put firms at a disadvantage; research suggest that firms that are ambidextrous or those that are able to develop both exploitative and exploratory innovations tend to perform better (Durisin and Todorova, ; O'Reilly and Tushman, , ). However, there has been little research that examines how firms can augment their exploration or exploitation capability (DiMasi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that the ability to codify tacit knowledge as well as reliance on routines are radically different for different NPD tasks (Benner and Tushman, 2003;Durisin and Todorova, 2012). For example, Benner and Tushman (2003) found communication linkages varied by project type.…”
Section: Project Typementioning
confidence: 99%
“…For example, Benner and Tushman (2003) found communication linkages varied by project type. In their longitudinal study, Durisin and Todorova (2012) found two units pursuing radically different project types developed very different embedded routines.…”
Section: Project Typementioning
confidence: 99%